2022
DOI: 10.3390/technologies10010011
|View full text |Cite
|
Sign up to set email alerts
|

Water-Assisted Perovskite Quantum Dots with High Optical Properties

Abstract: Lead halide perovskite quantum dots (PeQDs) have excellent optical properties, such as narrow emission spectra (FWHM: 18–30 nm), a tunable bandgap (λPL: 420–780 nm), and excellent photoluminescence quantum yields (PLQYs: >90%). PeQDs are known as a material that is easily decomposed when exposed to water in the atmosphere, resulting in causing PeQDs to lower performance. On the other hand, according to the recent reports, adding water after preparing the PeQD dispersion decomposed the PeQD surface defects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…13,14,[17][18][19] However, it has been reported that incorporating trace amounts of water during the synthesis step can result in more stable IPNCs with high PLQY. [20][21][22][23][24][25][26] Several different mechanisms have been proposed to explain this observation. For example, it was reported that addition of trace amount of water to the reaction mixture reportedly decrease the surface defects on IPNCs, thus improving the luminescence quantum yield.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…13,14,[17][18][19] However, it has been reported that incorporating trace amounts of water during the synthesis step can result in more stable IPNCs with high PLQY. [20][21][22][23][24][25][26] Several different mechanisms have been proposed to explain this observation. For example, it was reported that addition of trace amount of water to the reaction mixture reportedly decrease the surface defects on IPNCs, thus improving the luminescence quantum yield.…”
Section: Resultsmentioning
confidence: 97%
“…For example, it was reported that addition of trace amount of water to the reaction mixture reportedly decrease the surface defects on IPNCs, thus improving the luminescence quantum yield. 22 Others reported, the formation of highly bright IPNCs from non-luminescent perovskite structure at the interface of polar (water) and non-polar solvent (hexane, toluene, chloroform) due to the stripping of excess CsX. 25 In a typical LARP method, non-polar solvent such as toluene, hexane is considered as "poor solvent" that is known to increase the degree of supersaturation inducing formation of nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been shown that addition of water during the synthesis process can improve the photophysical properties of CsPbBr 3 NCs [17,[22][23][24][25][26][27][28]. For example, formation of CsPbX 3 NC from non-luminescent Cs-rich Cs 4 PbX 6 nanocrystals in presence of water [25].…”
Section: Resultsmentioning
confidence: 99%
“…[ 76 ] The loss of these highly dynamic ligands during processing can initiate undesired Ostwald ripening process and destabilize the NCs. [ 77 ] Therefore, optimization of ligand binding and surface coverage plays an important role in improving the colloidal stability and optical properties of HP NCs. [ 78 ] A small change in the concentration and ratio of the employed ligands such as oleic acid and oleylamine affects the physical properties and phase of the HP NCs.…”
Section: Synthesis Approaches For Preparation Of Hp Ncsmentioning
confidence: 99%